A neuroeconomic investigation of 5-HTT/5-HT1A gene variation, social anxiety, and risk-taking behavior. Issue 2 (3rd March 2020) - Stamatis, Caitlin A.; Engelmann, Jan B.; Ziegler, Christiane; Domschke, Katharina; Hasler, Gregor; Timpano, Kiara R.
ABSTRACT: Background and objectives: Although approaches combining behavioral genetics and neuroeconomics have advanced models of addiction, no study has synthesized these methods to elucidate mechanisms of competing risk-approachand risk-avoidance in social anxiety (SA). Grounded in dual-mode models of serotonergic systems and self-regulation, this study investigated associations between SA, serotonin transporter 5-HTT (LPR; rs25531) and receptor 5-HT1A genes, and risk-taking on behavioral and self-report measures. Design and methods: Young adults ( N  = 309) completed a neuroeconomic task measuring gambling attractiveness ( δ ), reward probability discrimination ( γ ), and risk attitudes ( α ). Risk genotypes included 5-HTT (LPR; rs25531) low-expression variants (SS/SLG /LG LG ), and 5-HT1A (rs6295) GG. Results: Path analysis revealed that SA related to increased gambling attractiveness, but only for 5-HT1A risk groups. Although the 5-HTT (LPR; rs25531) risk genotypes and self-reported SA predicted lower social risk-taking, high-SA individuals who exhibited more accurate reward probability discrimination ( γ ) reported taking increased social risks. Conclusion: In line with dual-mode models, results suggest that SA predicts behavioral risk-approach at the basic decision-making level, along with self-reported social risk-avoidance, modulated by serotonergic genotypes. High-SA individuals with more accurate assessments of reward probabilities may engage in greater social risk-taking, perhaps reflecting an adaptive tendency to approach feared situations.